Inhibitory Activity of Probiotic Milk Against Eschericia coli ATCC 6538 and Staphylococcus aureus ATCC 8739 - Andyanita Hanif Hermawati; Aryati Aryati; Isnaeni Isnaeni (Berkala Ilmiah Kimia Farmasi, 2020)
The aim of this research is to evaluate inhibitory activity of Lactobacillus acidophilus (L.a) and Lactobacillus casei (L.c) probiotic milk against Escherichia coli and Staphylococcus aureus growth. The fermented milk was prepared by inoculating each probiotic in milk at 43ºC and then incubated at room temperature for 24 hours. Diffusion agar method by using nutrient agar media was used to assess the minimum inhibition concentration (MIC). Obtained results showed pH of fermentation probiotic milk 5 + 0,05. Optimum inhibition zone diameter of L. acidophilus fermented milk against Escherichia coli and Staphylococcus aureus at MIC value of 14 mm. Inhibition zone diameter of L. casei fermented milk obtained an optimum against Escherichia coli and Staphylococcus aureus at MIC value of 12 mm and 13 mm respectively. The L. acidophilus and Lactobacillus casei probiotics fermented milk exhibited considerable antibacterial agent against Escherichia coli and Staphylococcus aureus.